Identifying surface reaction intermediates with photoemission tomography - Xiaosheng Yang (Nature Portfolio, 2019)
Identifying reaction pathways is a major challenge in chemistry, and proves particularly difficult for surface reactions. Here the authors show that imaging the molecular orbitals with photoemission tomography provides insight into the structure of surface intermediates allowing their identification.